2009
DOI: 10.1093/icesjms/fsp106
|View full text |Cite
|
Sign up to set email alerts
|

Anthropogenic and natural effects on the coastal lagoons in the southwest of Spain (Doñana National Park)

Abstract: Sousa, A., García-Murillo, P., Morales, J., and García-Barrón, L. 2009. Anthropogenic and natural effects on the coastal lagoons in the southwest of Spain (Doñana National Park). – ICES Journal of Marine Science, 66: 1508–1514. The Doñana peridunal lagoons, located in the southwest of Spain, have been well studied, because their conservation is of great interest. Since 1965, they have also been affected by the extraction of underground water for local coastal tourist resorts. A reconstruction of the evolution … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
19
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 16 publications
1
19
0
Order By: Relevance
“…Some studies in south-western Europe have shown that the potential influence of climate change on continental aquatic ecosystems can contribute to intensifying the pre-existing impacts of anthropogenic influence (Álvarez-Cobelas et al 2005, Álvarez-Cobelas 2007. These estimates are consistent with studies examining the impact of past climate periods such as the Little Ice Age (Sousa & García-Murillo 2003, Sousa et al 2006 or climatic variations at the end of the late 19 th /early 20 th century in different aquatic ecosystems in the south of the Iberian Peninsula (Sousa et al 2009(Sousa et al , 2010.…”
Section: Discussionsupporting
confidence: 89%
“…Some studies in south-western Europe have shown that the potential influence of climate change on continental aquatic ecosystems can contribute to intensifying the pre-existing impacts of anthropogenic influence (Álvarez-Cobelas et al 2005, Álvarez-Cobelas 2007. These estimates are consistent with studies examining the impact of past climate periods such as the Little Ice Age (Sousa & García-Murillo 2003, Sousa et al 2006 or climatic variations at the end of the late 19 th /early 20 th century in different aquatic ecosystems in the south of the Iberian Peninsula (Sousa et al 2009(Sousa et al , 2010.…”
Section: Discussionsupporting
confidence: 89%
“…The system of ponds on Doñana's aeolian sands is a good example of Mediterranean temporary ponds. They have been declining with climate change by an increased aridification since the "Little Ice Age" [10][11][12]53,54] but have also been suffering an increased anthropogenic pressure [1,55]. It has been documented how groundwater abstraction for agriculture [13] or for tourism resorts has negatively influenced or dessicated certain ponds in the system [34].…”
Section: Discussionmentioning
confidence: 99%
“…Intensive land use and groundwater exploitation or drainage have led to deterioration of springs (e.g. Howe, 2002), coastal wetlands (Halvorson et al, 2003), lagoons (Sousa et al, 2009), headwater lakes and peatlands (Kvaerner & Snilsberg, 2008).…”
Section: Introductionmentioning
confidence: 99%